Relationships between sleeve trial and wearer trial assessment of discomfort and objective measurements. Issue 3 (February 2015) - McGregor, Bruce A; Doyle, Emma; Thompson, John; Naebe, Maryam; Speijers, Jane; Tester, David
The relationships were investigated between the prickle discomfort scores, assessed by human response from wearer trial garment assessment, and sleeve trial, Wool ComfortMeter (WCM) and Wool HandleMeter (WHM) assessments of fabrics, and fiber diameter characteristics including mean fiber diameter (MFD). Sleeve trial assessment followed exercise, the use of a control sleeve to reduce participant variance and four sensory traits. WHM provides eight handle parameters calibrated against a panel of experts. Four scenarios were evaluated: sleeve trial assessment with MFD; sleeve trial assessment with MFD and WCM; sleeve trial assessment with MFD, WCM and WHM parameters; and sleeve trial assessment with WCM and WHM parameters. Data were analyzed using correlation and forward stepwise general linear modeling. There was no evidence that the incidence of fibers coarser than 30 µm aided the prediction of prickle discomfort once MFD had been accounted for in the models. There were significant correlations between the WCM measurement and each sleeve trial attribute. There was no significant correlation between WHM parameters and sleeve trial assessments. The sleeve trial attribute of 'skin feel' offers potential to improve the predictions made of wearer trial prickle discomfort when used in association of the WCM with or without data on fabric MFD. There was little evidence to support using WHM parameters with or without the WCM in predicting wearer assessed prickle discomfort of fabrics. These results indicate that the rapid evaluation of fabrics using sleeve trial assessment can provide cost effective ranking of consumer preferences.